Predictors of significant coronary artery disease in atrial fibrillation: Are cardiac troponins a useful measure. (15th November 2016) - Alghamry, Alaa; Hanna, Joseph; Pelecanos, Anita; Kyranis, Stephen; Khelgi, Vinod; O'Rourke, Peter; Carroll, Oran; Oxenford, Cassie; Rangaswamaiah, Swetha; Tan, Christopher
Abstract: Background: Cardiac Troponin I (cTnI) is frequently measured in patients presenting with symptomatic atrial fibrillation (AF). The significance of elevated cTnI levels in this patient cohort is unclear. We investigated the value of cTnI elevation in this setting and whether it is predictive for significant coronary artery disease (sCAD). Methods: We conducted a retrospective, single-center, case–control study of 231 patients who presented with symptomatic AF to The Prince Charles Hospital emergency department, Brisbane, Australia between 2006 and 2014. Patients who underwent serial cTnI testing and assessment for CAD were included. Clinical variables that are known to predict CAD and could potentially predict cTnI elevation were collected. Binary logistic regression was performed to identify predictors of sCAD and cTnI elevation. Results: Cardiac Troponin I elevation above standard cut off was not predictive for sCAD after adjustment for other predictors (OR 1.62, 95% CI 0.79–3.32. p = 0.19). However, the highest cTnI concentration value (cTnI peak) was predictive for sCAD (OR 2.02, 95% CI 1.02–3.97, p = 0.04). Dyspnea on presentation (OR 4.52, 95% CI 1.87–10.91, p = 0.001), known coronary artery disease (OR 3.44, 95% CI 1.42–8.32, p = 0.006), and ST depression on the initial electrocardiogram (OR 2.57, 95% CI 1.11–5.97, p = 0.028) predicted sCAD in our cohort, while heart rate on initial presentation was inversely correlated with sCAD (OR 0.99, 95% CI 0.971–1.00, p = 0.034). Conclusion: Troponin elevation is common in patients presenting to hospital with acute symptomatic AF and it is not a reliable indicator for underlying sCAD in this patient cohort. However, cTnI peak was a predictor of significant coronary artery disease.